Completion of the continuum of maternity care and associated factors among women who gave birth in the last 6 months in Chelia district, West Shoa zone, Ethiopia: A community-based cross-sectional study - Buli, Temesgen Daksisa; Wakgari, Negash; Ganfure, Gemechu; Wondimu, Fikadu; Dube, Dereje Lemma; Moti, Gonfa; Doba, Yonas Sagni (Frontiers in Public Health, 2023)
Background: The continuum of maternity care is a continuity of care that a woman receives during pregnancy, childbirth and postpartum period from skilled providers in a comprehensive and integrated manner. Despite existing evidence regarding maternal health care services discretely, the continuum of maternity care and its associated factors are not well known in Ethiopia. Objective: This study assessed the completion of maternity continuum of care and associated factors among women who gave birth 6 months prior to the study in Chelia district. Methods: A community based cross-sectional study with a stratified random sampling technique was conducted among 428 mothers at ten randomly selected kebeles. Pretested and structured questionnaires were used to collect data. Bivariable and multivariable logistic regression analysis were performed to identify associated factors. Adjusted odds ratio with its 95% confidence interval was used to determine the degree of association and statistical significance was declared at a p-value of < 0.05. Results: In this study, 92 (21.5%) of mothers completed the continuum of maternity care. Secondary and above education of mothers (AOR=4.20, 95% CI:1.26-13.97), <30 minutes’ spent on walking by foot (AOR=4.00, 95% CI: 1.67-9.58) and use of ambulance to reach health facility(AOR=3.68, 95% CI: 1.23-11.06), para>5 mothers (AOR=0.21, 95% CI: 0.05-0.90), planned pregnancy (AOR=3.29, 95% CI: 1.02-10.57), attending pregnant women’s conference (AOR=13.96, 95% CI: 6.22-31.30), early antenatal care booking (AOR=3.30, 95% CI: 1.54-7.05), accompanied by partners (AOR=3.64, 95% CI: 1.76-7.53), and informed to return for postnatal care (AOR=3.57, 95% CI: 1.47-8.70) were the factors identified. Conclusion: In this study, completion maternity of continuum of care was low. Therefore, appropriate strategic interventions that retain women in the continuum of maternity care by targeting those factors were recommended to increase uptake of the continuum of maternity care.